2021
DOI: 10.1021/acs.jafc.1c04204
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Dietary Vitamin D3 Supplementation on Growth, Molting, Antioxidant Capability, and Immunity of Juvenile Chinese Mitten Crabs (Eriocheir sinensis) by Metabolites and Vitamin D Receptor

Abstract: ), as an indispensable and fat-soluble nutrient, is associated with skeletal mineralization and health in mammals. However, such associations have not been well studied in economically important crustaceans. Six levels of vit-D 3 with isonitrogenous and isolipidic diets were used to feed Eriocheir sinensis. The range of optimal vit-D 3 requirements is 5685.43−10,000 IU/kg based on growth. The crabs fed 9000 IU/kg vit-D 3 showed the best growth performance. This vit-D 3 dose significantly increased antioxidant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 48 publications
3
9
0
Order By: Relevance
“…In addition, the in vivo results showed that VD 3 deficiency contributed to the reduced intestinal immune-related enzyme activities of ACP, ALP, and LYZ activities. These results showed that the deficiency of VD 3 in diet could induce intestinal enteritis of turbot, which was consistent with the previous studies that diets with sufficient VD 3 are the basis for maintaining intestinal immune function, and VD 3 deficiency provoked an intestinal inflammatory response in European sea bass ( Dicentrarchus labrax L.) and Chinese mitten crabs ( 5 , 8 ).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In addition, the in vivo results showed that VD 3 deficiency contributed to the reduced intestinal immune-related enzyme activities of ACP, ALP, and LYZ activities. These results showed that the deficiency of VD 3 in diet could induce intestinal enteritis of turbot, which was consistent with the previous studies that diets with sufficient VD 3 are the basis for maintaining intestinal immune function, and VD 3 deficiency provoked an intestinal inflammatory response in European sea bass ( Dicentrarchus labrax L.) and Chinese mitten crabs ( 5 , 8 ).…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, VDR deletion in intestinal epithelial cells leads to the decreased expression of claudin 2 and 12 in the intestine of mice and intestinal cell line Caco-2 ( 15 ). In addition, the activation of the NF-κB pathway by VD 3 was also observed in juvenile Chinese mitten crabs ( Eriocheir sinensis ) that VD 3 might improve intestinal immunity via the VDR/TLR/MyD88/NF-κB pathway ( 5 ). However, whether VD 3 /VDR mediated intestinal barrier function and NF−κB signalling pathway involved in regulating intestinal inflammation is not comprehensively understood in the teleost.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Current research on the regulation of E. sinensis molting focuses mainly on the influence of external environmental factors and nutritional elements, including temperature, pH, vitamins, etc. ( Yu et al, 2018 ; Chen et al, 2019 ; Wang et al, 2020a ; Liu et al, 2021a ; Zhang et al, 2021 ). Moreover, the role of several regulatory genes such as V-ATPase subunit B (VATB), transforming growth factor-beta type I receptor (TGFBR1) and S6 kinase has also been studied ( Tian et al, 2019 ; Hou et al, 2020 ; Tian et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%